2020
DOI: 10.1021/acsami.0c05576
|View full text |Cite|
|
Sign up to set email alerts
|

Sr2NiWO6 Double Perovskite Oxide as a Novel Visible-Light-Responsive Water Oxidation Photocatalyst

Abstract: Screening of stable visible-light-responsive water oxidation semiconductor photocatalysts is highly desired for the development of photocatalytic water splitting systems. Herein, a visible-light-absorbing Sr2NiWO6 double perovskite oxide photocatalyst was successfully prepared via a conventional solid-state reaction method. The intrinsic Sr2NiWO6 shows photocatalytic oxygen evaluation reaction (OER) activity of 60 μmol h–1 g–1, even without loading any cocatalysts. The DFT calculation indicates that the Ni spe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
35
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 58 publications
(35 citation statements)
references
References 53 publications
0
35
0
Order By: Relevance
“…To determine the band edge positions, the flat‐band potential of the ScTaO 4 and ScTaO 4−x N x samples were firstly evaluated from the Mott‐Schottky (MS) plots in an aqueous Na 2 SO 4 solution (pH=7). As shown in Figure 2d and Figure S6, MS plots with positive slope imply the as‐prepared ScTaO 4 and ScTaO 4−x N x are n‐type conducting semiconductors, [30] and the flat band potential can be calculated to be ca. −0.08 and −0.10 V vs. NHE (pH=0), respectively.…”
Section: Figurementioning
confidence: 94%
“…To determine the band edge positions, the flat‐band potential of the ScTaO 4 and ScTaO 4−x N x samples were firstly evaluated from the Mott‐Schottky (MS) plots in an aqueous Na 2 SO 4 solution (pH=7). As shown in Figure 2d and Figure S6, MS plots with positive slope imply the as‐prepared ScTaO 4 and ScTaO 4−x N x are n‐type conducting semiconductors, [30] and the flat band potential can be calculated to be ca. −0.08 and −0.10 V vs. NHE (pH=0), respectively.…”
Section: Figurementioning
confidence: 94%
“…To promote the activity of g-C 3 N 4 and make it more practical, numerous strategies have been developed, including nanostructure engineering, metal/nonmetal doping, protonating by strong acids, and fabrication of heterojunction composites. Moreover, it is confirmed that surface modification with proper cocatalysts is a valid way to accelerate charge separation and reduce the activation energy for H 2 or O 2 evolution, leading to an excellent photocatalytic activity . However, to date, the most commonly used cocatalysts are still those rare and expensive noble metals and oxides (such as Pt, Pd, and RuO 2 ), which greatly restricts their practical applications. , Considering the cost and practicability, it is meaningful to develop high active cocatalysts without noble metals.…”
Section: Introductionmentioning
confidence: 99%
“…14 However, to date, the most commonly used cocatalysts are still those rare and expensive noble metals and oxides (such as Pt, Pd, and RuO 2 ), which greatly restricts their practical applications. 15,16 Considering the cost and practicability, it is meaningful to develop high active cocatalysts without noble metals.…”
Section: Introductionmentioning
confidence: 99%
“…A variety of strategies have been explored to achieve efficient charge separation and transfer in semiconductor photocatalysis, such as heterojunction, [ 3 ] phase junction, [ 4 ] Z‐scheme, [ 5 ] and deposition of appropriate redox cocatalysts on the surface of semiconductor photocatalysts. [ 6–8 ] We are particularly interested in engineering and exploiting the intrinsic electric field of semiconductor as driving force for separation of photogenerated charges, and further enhance the photocatalytic activity by combination with the above mentioned traditional strategies. For example, we have shown that photogenerated charges can be efficiently separated on the different facets of a single semiconductor nanocrystal driven by in situ generated internal electric field, and spatial loading of redox cocatalysts on the different facets results in dramatically improvement of photocatalytic water oxidation activity.…”
Section: Introductionmentioning
confidence: 99%